2008
DOI: 10.1210/en.2008-0457
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Iodothyronine Deiodinase Is Essential for Thyroid Hormone-Dependent Embryonic Development and Pigmentation in Zebrafish

Abstract: Despite the known importance of thyroid hormones (THs) in vertebrate growth and development, the role of tissue-specific TH activation in early embryogenesis remains unclear. We therefore examined the function of type 2 iodothyronine deiodinase (D2), one of the two tissue-specific enzymes catalyzing the conversion of T4 to T3, in developing zebrafish embryos (Danio rerio). Microinjection of early embryos with antisense oligonucleotides targeting either the D2 translation start site or the splice junction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 37 publications
2
61
2
Order By: Relevance
“…However, lesser concentration of T4 and T3 were detected in this study, which might be attributed to (1) MCLR might inhibit synthesis of T3 and T4; (2) MCLR could block conversion of T4 to T3 like other endocrine-disrupting chemicals (van der Ven et al, 2006;Liu et al, 2011). Whereas, Deio2 is present in brain, pituitary and thyroid, and its transcription has been associated with the levels of circulating T4 and TH homeostasis in tissues (Walpita et al, 2009). In a recent study, Deio2 knockdown led to a dramatic development delay in zebrafish embryos/ larvae, whereas knockdown of Deio1 did not affect developmental progression (Walpita et al, 2009).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, lesser concentration of T4 and T3 were detected in this study, which might be attributed to (1) MCLR might inhibit synthesis of T3 and T4; (2) MCLR could block conversion of T4 to T3 like other endocrine-disrupting chemicals (van der Ven et al, 2006;Liu et al, 2011). Whereas, Deio2 is present in brain, pituitary and thyroid, and its transcription has been associated with the levels of circulating T4 and TH homeostasis in tissues (Walpita et al, 2009). In a recent study, Deio2 knockdown led to a dramatic development delay in zebrafish embryos/ larvae, whereas knockdown of Deio1 did not affect developmental progression (Walpita et al, 2009).…”
Section: Discussioncontrasting
confidence: 53%
“…Whereas, Deio2 is present in brain, pituitary and thyroid, and its transcription has been associated with the levels of circulating T4 and TH homeostasis in tissues (Walpita et al, 2009). In a recent study, Deio2 knockdown led to a dramatic development delay in zebrafish embryos/ larvae, whereas knockdown of Deio1 did not affect developmental progression (Walpita et al, 2009). The results showed that Deio2 might be the major contributor to TH activation in developing zebrafish embryos/larvae, suggesting the decreased Deio2 transcription in the present study may affect zebrafish development.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, it has been demonstrated that dio2, expressed at the early embryonic stages, plays a pivotal role in deiodination and production of active T 3 , which ensures an adequate availability of local and systemic T 3 (Walpita et al, 2009). Previous reports showed that, in fish, hyperthyroidism suppressed dio2 mRNA expression and activity, while hypothyroidism increased dio2 mRNA expression and activity (Van der Geyten et al, 2005;Walpita et al, 2009). Upregulation of dio2 by BDE-209 with presence of nano-TiO 2 is consistent with our previous notion that deiodinases can be evaluated to investigate thyroid endocrine disruption by PBDEs, which may also explain the elevated levels of T 3 observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that deiodination may play a role in altering the homeostasis of THs. It has been recently demonstrated that in zebrafish, the expression of Deio2 during the early embryonic stages plays a pivotal role in producing T3, increasing the availability of local and systemic T3 (Walpita et al, 2009). It appears plausible that an increase in the transcription of Deio2 may, at least partly, be associated with a reduction in the levels of circulating T4 and have a significant impact on TH homeostasis in tissues.…”
Section: Discussionmentioning
confidence: 99%